Substantial Contribution of SmeDEF, SmeVWX, SmQnr, and Heat Shock Response to Fluoroquinolone Resistance in Clinical Isolates of Stenotrophomonas maltophilia - Wu, Chao-Jung; Lu, Hsu-Feng; Lin, Yi-Tsung; Zhang, Man-San; Li, Li-Hua; Yang, Tsuey-Ching (Frontiers in Microbiology, 2019)
Stenotrophomonas maltophilia is an emerging multi-drug resistant opportunistic pathogen. Although fluoroquinolones (FQ) are still clinically valuable for the treatment of S. maltophilia infection, an increasing prevalence in FQ resistance has been reported. Overexpression of SmeDEF, SmeVWX, and SmQnr, and de-repressed expression of heat-shock response are reported mechanisms responsible for FQ resistance in S. maltophilia; nevertheless, some of these mechanisms are identified from laboratory-constructed mutants, and it remains unclear whether the occur in clinical setting. In this study, we aimed to assess whether these mechanisms contribute substantially to FQ resistance in clinical isolates. Eighteen ciprofloxacin- and levofloxacin-resistant isolates were selected from 125 clinical isolates of S. maltophilia. The expression of smeE, smeW, and Smqnr genes of these isolates was investigated by RT-qPCR. The de-repressed heat-shock response was assessed by rpoE expression at 37C and bacterial viability at 40C. The contribution of SmeDEF, SmeVWX, and SmQnr, and heat shock response to FQ resistance was evaluated by mutants construction and susceptibility testing. The results demonstrated that simply assessing the overexpression of SmeDEF, SmeVWX, and SmQnr by RT-qPCR may overestimate their contribution to FQ resistance. Simultaneous overexpression of SmeDEF and SmeVWX did not increase the resistance level to their common substrates, but extended the resistance spectrum. Moreover, the de-repressed expression of heat shock response was not observed to contribute to FQ resistance in the clinical isolates of S. maltophilia.